WISATA MINAT KHUSUS: MENGUAK KEHIDUPAN MASYARAKAT JAWA KUNA MELALUI RELIEF CANDI - Hari Lelono (Berkala Arkeologi, 2012)
There are still some tourism potentials not yet entirely discovered to the public and to the tourists, specifically to the special interest type of these tourists. The potential object will be discussed on this paper relates to the cultural content which is carved over the temple’s walls through the decorative reliefs reflecting the reality or any information about the temple itself and its era. Through the reliefs, many information about the daily live of the ancient Javanese people are revealed. Besides that, the reliefs also describe the species variety of vegetation and animal, the clothes and its supporting ornaments as well as the story or fable which is containing of the original cultural values of Indonesia including the moral messages which give our nation an identity and integrity. The moral values or contents should be offered to the tourists so they could understand the original culture of Indonesia by not only enjoying the physical aspect of any objects (tangible) but more over the intangible aspect which gives a spirit into those objects.